ACCURACY OF THE DOPPLER RESISTIVE INDEX IN THE DIAGNOSIS OF MALIGNANT BREAST MASSES: Malignant Breast Masses - Aziz, Sadaf; Haq, Arfan -ul-; Ahmad, Asad Maqbool (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the accuracy of the resistive index in the diagnosis of malignant breast masses using histopathology as the gold standard. Study Design: Validation study. Place and Duration of Study: Radiology department, PNS Shifa Karachi from 2nd February to 8th August 2007. Methods: Appropriate technical and ethical approval for the study and patient consent were obtained. Fifty three adult female patients (selected by non-probability purposive sampling) with ages ranging from 14 to 58 years presenting with one or more breast lumps at Radiology department, PNS Shifa Karachi, who subsequently underwent biopsy were included in the study. All patients underwent doppler ultrasonography by an experienced consultant radiologist. Doppler spectral parameters including the Resistive Index (RI) were calculated on all tumor vessels more than 3 mm long visible on Pulsed Doppler Sonography. The resistive indices for each patient were compared with the histopathology result, which was considered as gold standard. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the RI was calculated. Results: Thirty five (35) patients were found to be having benign lesions whereas 18 patients were having malignant lesions on histopathology examination. In the group that had benign lesions, the mean RI was 0.60 with a range of 0.45 to 0.78 whereas the median was 0.61. In the group, that had malignant lesions the mean RI was 0.76 with a range of 0.64 to 0.93 and the median was 0.74. The ROC curve lies close to the top left corner of the ROC space and has a significant area under the curve (AUC) of 0.955 with a p-value of less than 0.001. Conclusion: The Resistive Index (RI) is an accurate diagnostic tool and may therefore be used in the diagnosis of carcinoma breast during evaluation of breast lumps in adult females. An RI of 0.675 is an adequate cut-off value that is both sensitive (94.4%) and specific (91.4%) enough to diagnose malignancy with a false positive rate of 8.6% and a false negative rate of 5.6%.